Ethics of personalized information filtering - Koene, Ansgar; Perez, Elvira; Carter, Christopher J.; Statache, Ramona; Adolphs, Svenja; O’Malley, Claire; Rodden, Tom; McAuley, Derek (Springer Verlag, 2015)
Online search engines, social media, news sites and retailers are all investing heavily in the development of ever more refined information filtering to optimally tune their services to the specific demands of their individual users and customers. In this position paper we examine the privacy consequences of user profile models that are used to achieve this information personalization, the lack of transparency concerning the filtering choices and the ways in which personalized services impact the user experience. Based on these considerations we argue that the Internet research community has a responsibility to increase its efforts to investigate the means and consequences of personalized information filtering.